Changes in the microstructure and properties of aspen chemithermomechanical pulp fibres during recycling. (6th March 2015) - Fu, Yingjuan; Wang, Rongrong; Li, Dejuan; Wang, Zhaojiang; Zhang, Fengshan; Meng, Qinglin; Qin, Menghua
Highlights: CTMP behaved as chemical pulp rather than mechanical pulp during recycling. Cocrystallisation of cellulose microfibrils indeed occur in CTMP fibre. Many large pores and very small pores in the fibre wall closed. Single fibre strength increased but the interfibrebonding decreased. Abstract: The effects of recycling on the microstructure and properties of bleached aspen chemithermomechanical pulp (CTMP) fibres were systematically investigated. The low-temperature nitrogen adsorption and atomic force microscopy results showed that a substantial amount of large pores and most of the very small pores in the fibre wall closed and the fibre surface became less coarse and porous during recycling. The partial cocrystallisation of cellulose microfibrils took place, as reflected in the increment of the cellulose crystallinity and the width of the crystallite in the 0 0 2 lattice plane. These irreversible structural changes caused significant hornification of the recycled fibres, leading to the loss of swelling and bonding capability. The decrease of the tensile index, burst index, and tear index further demonstrated the deterioration of the fibre properties. However, the single-fibre strength considerably increased after recycling, which was mainly due to the enlarged cellulose aggregates in the fibre wall.